Comparative Impact of Traditional and Modern Promotion on Brand Equity Dimensions - Shrestha, Bandana; Shrestha, Binod Krishna (Nepalese Journal of Management and Technology, 2024)
This research study aimed at investigating the differential impact of traditional and modern promotion on brand equity dimensions such as brand awareness, perceived quality, brand image, and brand loyalty. The findings provide valuable insights into the effectiveness of these promotional strategies in enhancing brand equity. The findings show that compared to traditional promotional tools, modern promotional tools have a greater impact on brand equity dimensions. These findings have significant implications for marketers and advertisers, highlighting the necessity of modifying promotional tactics to take advantage of modern technology and online platforms.